Effect of 29 weeks of periodized soccer training on the neuromuscular performance of soccer players under 20 years of age - Corrêa, Daniel Alves; Soares, Danilo Saad; Gonelli, Pamela R.G.; Cesar, Marcelo de C.; Germano, Moisés D.; Sindorf, Marcio A.G.; Crisp, Alex Harley [UNESP]; Verlengia, Rozangela; Balbino, Hermes Ferreira; Lopes, Charles Ricardo (My University, 2016)
The purpose of this study was to investigate the effects of 29 weeks of periodized soccer training (linear during pre-season and ondulatory during the competitive period) on the neuromuscular performance of soccer players under 20 yrs of age. Ten regionally ranked male athletes (19.2 ± 1.3 yrs, body mass 71.1 ± 6.8 kg, height 179.0 ± 0.2 cm) participated in this study. The pre-season physical training program lasted 9 wks. The competitive period lasted 19 wks. The assessments were conducted at specific times during training periodization: baseline, 4, 8, and 19 wks. The results showed improvements in squat jump performance and maximal strength during the pre-season and the competitive period, respectively. On the other hand, repeated sprint ability and the 15-m sprint performance were reduced at the end of competitive period. Thus, the findings indicate that 29 wks of periodized soccer training increased the soccer players' maximum strength and maintained their vertical jump performance. However, the models adopted did not improve repeated sprint ability and the 15-m sprint time.
Keywords: Periodization; Soccer; Sports training; Sprint